Optimization of the Role of Job Satisfaction on the Effect of Leadership Effectiveness on Employee Performance - Sriyanto Sriyanto; Sutianingsih Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to understand how job satisfaction can mediate between leadership effectiveness and employee performance. In this study, quantitative research methods were used. Data were collected with the help of questionnaires and a sample of 115 employees. Path analysis and descriptive analysis are the data analysis methods used. Research findings show that all variables have a positive effect can be seen from 1) leadership effectiveness has an impact on job satisfaction variables. 2) Leadership effectiveness has an impact on employee performance. 3) Job satisfaction has an impact on employee performance. 4) The results of this study state that indirect influence is more potent than direct influence. Then job satisfaction is used as an intermediary between job placement variables and employee performance. Keywords: leadership effectiveness, job satisfaction, Performance